2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090532
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate, oxygen saturation, and skin conductance: A comparison study of acute pain in Brazilian newborns

Abstract: Heart rate variability (HRV), oxygen saturation variability (OSV) and skin conductance activity (SCA) are recognized physiological markers of acute pain. In order to verify which of them has the best correlation with psychophysical parameters of pain (intensity, reactivity, direction, regulation and slope), an observational prospective study was performed, including 41 healthy full term newborns. The measurements studied were the HRV, the OSV, and the following SCA variables: number of waves per second (NWps) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 29 publications
0
30
0
2
Order By: Relevance
“…Another retrospective study also reported that tissue-damaging during a heel stick procedure. 101,103 Heart rate variability is an appropriate measure of response to acute pain and prolonged pain in neonates 22,[104][105][106] ; however, given a lack of the availability of monitoring devices, it may not be clinically applicable.…”
Section: Such As the Neonatal Facialmentioning
confidence: 99%
“…Another retrospective study also reported that tissue-damaging during a heel stick procedure. 101,103 Heart rate variability is an appropriate measure of response to acute pain and prolonged pain in neonates 22,[104][105][106] ; however, given a lack of the availability of monitoring devices, it may not be clinically applicable.…”
Section: Such As the Neonatal Facialmentioning
confidence: 99%
“…It is in AS that the maturation and differentiation of the CNS and memory consolidation occur and learning patterns of emotional behavior develop 7,12,13,16,17 . QS, compatible with Non Rapid Eye Movement sleep (NREM) in adults, is already identified in the electroencephalogram at 32 weeks of gestation, but is only well developed in the [36][37][38] th week of gestation. It is formed after stabilization networks of specific excitatory and inhibitory components of the thalamus and cortex.…”
Section: Sleep and Prematuritymentioning
confidence: 99%
“…It is therefore difficult to propose, for each type of existing measure, a cut off point or the absolute threshold of pain. Hence, the great variability between the responses of children does not allow a universal score for pain 38 . The dimensions of these physiological indicators can be described through psychophysical parameters of intensity, direction, reactivity, regulation and slope.…”
Section: Pain Measurements In Neonatal Intensive Care Unitmentioning
confidence: 99%
“…The baseline value was determined from a stable 10 seconds prior to the start of the procedure. For GSR, we recorded area under small peaks and peaks per second during the first 30 seconds after start of the procedure . Also for PIPP‐R, the assessment time was the first 30 seconds from start of the procedure …”
Section: Methodsmentioning
confidence: 99%
“…Galvanic skin response measures skin conductance due to “emotional sweating” which reflects pain‐related activation of the sympathetic nervous system and has been used to measure neonatal pain in studies on term and preterm infants. Analyses of GSR are presented with a number of different variables, where area under small peaks and peaks per second has been shown to reflect pain in premature and term infants …”
Section: Introductionmentioning
confidence: 99%